Implementation of Family Learning Center Program Services in Penjaringan Sari Village RW.04, Surabaya City - Yuwanita Nurmasari; Dinda Maura Prameswari; Annisya Rossita Palupi; Annisa Wulandari (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
Abstract The family plays an important role in the formation of children's character and the social resilience of the community. To support this function, the Surabaya City Government organizes the Family Learning Center Program (PUSPAGA) at the community level as a form of educational, consultative, and preventive services. This study aims to examine the implementation of PUSPAGA services in RW.04, Penjaringan Sari Village, Surabaya City, using a descriptive qualitative approach. Data collection techniques were carried out through interviews, direct observations in the field, and important and relevant documentation. The results of the study showed that the implementation of the program faced various challenges, such as uneven communication, the absence of written technical instructions, and learning methods that tended to be one-way. However, active community participation and the commitment of the implementers were the main strengths in maintaining the sustainability of activities. Meanwhile, the bureaucratic structure that was not yet equipped with Standard Operating Procedures (SOP) caused inconsistencies in implementation. These findings indicate the importance of an in-depth understanding of the dynamics of the implementation of community-based family service programs. Keywords: Community Participation, Implementation, PUSPAGA